A novel strategy to fabricate a hierarchical Ni–Al LDH platinum nanocatalyst with enhanced thermal stability. (25th July 2017) - Zhang, Chao; Zhou, Yuming; Zhang, Yiwei; Fang, Jiasheng
Abstract : A novel strategy has been proposed to fabricate a hierarchical Ni–Al LDH platinum nanocatalyst (LDH-Pt). Abstract : A novel strategy has been proposed to fabricate a hierarchical Ni–Al LDH platinum nanocatalyst (LDH-Pt). The formation mechanism involves loading of Pt NPs on nanocarbon spheres (NCSs) and calcination of NCSs/Pt/Al2 O3 to remove inner NCSs. Then, Ni–Al LDH nanosheets in situ grew from hollow Pt/Al2 O3 nanoclusters via a hydrothermal process, eventually fabricating the hierarchical LDH-Pt nanocatalyst. TEM and SEM images were employed to characterize each step of the synthesis process. During the hydrothermal process, most of the Pt NPs in Al2 O3 shells were inlaid in the in situ grown LDH nanosheets, exhibiting a higher thermal stability than traditional impregnated LDH catalysts. Lastly, the as-synthesized LDH-Pt was tested with a high temperature reaction (590 °C) of propane dehydrogenation to further demonstrate the enhanced thermal stability of LDH-Pt.